Sociopreneurship Exhibition: Driving Inclusivity & Empowering Social Entrepreneurs Through Events - Ayundha Evanthi; Ilham Hardi (PT Inovasi Pratama Internasional, 2024)
Inclusive and diverse communities are vital for sustainable development. Supporting people with disabilities through community initiatives is crucial. Social entrepreneurship can be an effective tool for empowering individuals with disabilities and raising public awareness about social and economic diversity. This community service project in the form of Sociopreneurship Exhibition at Taman Bungkul Surabaya brought together people with disabilities, entrepreneurs, and the community The aim of this activity was to foster direct interaction between entrepreneurs and the wider community, and to provide a deeper understanding of the importance of inclusivity and diversity in social and economic life. The exhibition successfully raised public awareness of social inclusion and diversity, connected people with disabilities and entrepreneurs, and created opportunities for public participation in inclusive economic activities. The exhibition's interactive activities helped the public understand the importance of inclusivity and encouraged collaboration between entrepreneurs and people with disabilities. This not only promoted businesses but also raised public awareness about the significance of social inclusion in economic and social life